Seroprevalence of Infectious Markers for HIV, HBV, HCV, and Agent of Syphilis Among the Blood Donors At The Blood Transfusion Center of SOUK-AHRAS - AIDI Iness (My University, 2025)
In Algeria, the screening of blood donations for transfusion transmissible infections (TTIs) is obligatory and should be performed for every single blood unit collected. The unit with positive result for any markers for HIV, HBV, HCV, or Syphilis infections is discarded through incineration. This study aimed to determine the seroprevalence of these test results and identify their trends through the study period. A retrospective and descriptive study was conducted using summarized reports provided by the blood transfusion center of Souk-Ahras covering the period from January 2022 to December 2024 Of the total 5161 people who presented for blood donation, 4786 were accepted as legible donors with a 7.27% deferral rate in the study period. Male donors accounted for more than 79% of all blood donors and the proportions in donor type witnessed a shift in favor of voluntary non-remunerated donors. The overall seroprevalence displayed an increase during the study period with rates going from 0.20% in the first year to 4.65% in the third year. HBV infection was the most detected infection with two types of tests (Ag HBs and Anti HBc), wherein Anti-HBc test recorded the highest positivity rates with 4.28% in 2023 and 5.81% in 2024. The lowest rates were for both HIV and HCV tests that remained constant at zero for all years of the study. These findings highlight the importance of improved screening protocols and blood safety policies. Keywords: seroprevalence, blood donation, HIV, HBV, HCV, Syphilis -------------------------------------------------------------------------------------------------------------------------------------- يدور بحث المذكرة على الدراسة الميدانية حول مدى انتشار الامراض المتنقلة عبر نقل الدم بمصلحة حقن الدم التابعة للمؤسسة العمومية الاستشفائية كعرار السبتي بسوق اهراس. إن الكشف عن الامراض المتنقلة عبر نقل الدم إجباري لكل وحدة متبرع بها ويترتب عن نتائجه الموجبة التخلص من منها. نتائج البحث تم التوصل اليها من خلال معالجة التقارير السنوية الخاصة بمركز حقن الدم التي تلخص بيانات عمليات جمع الدم خلال الفترة الممتدة من جانفي 2022 إلى ديسمبر 2024. كانت النتائج كالاتي النسبة الاجمالية لرفض المتبرعين كانت 7.27% خلال فترة البحث كاملة. سجلت نسب التبرعات الطوعية تطورا ملحوظا من ضئيلة إلى أكثر من نصف التبرعات في العام 2024. المتبرعون الذكور مثلوا نسبة أكثر من 79% من مجموع المتبرعين. نسبة الأمراض المتنقلة عبر نقل الدم لدى المتبرعين كانت في تزايد مستمر خلال فترة البحث. فيروس لالتهاب الكبدي B سجل أعلى النسب ودلك في اختبار الكشف (HBcAc) .النسب الأقل كانت مسجلة لإختبارات الكشف عن فيروس الالتهاب الكبديC وفيروس فقدان المناعة المكتسبة اللدان سجلا صفر إختبار موجب خلال سنوات الدراسة كاملة. ------------------------------------------------------------------------------------------------------------------------------------- En Algérie, le dépistage des infections transmissibles par la transfusion est obligatoire pour tout don de sang. La poche de sang qui donne une réaction positive pour n’importe quel marqueurs viral HIV, HBV, HCV ou pour l’agent de Syphilis est éliminée par incinération. L’étude suivante a pour but la détermination des séroprévalences des résultats positives de ces tests et pour identifier leur évolution durant le temps de l’étude. Cette étude est rétrospective et descriptive, basée sur des rapports annuels du centre de transfusion sanguine de Souk-Ahras qui regroupent des données synthétiques de janvier 2022 jusqu’à décembre 2024. 4786 de donneurs ont été acceptés parmi un total de 5161 de personnes qui se sont présentés pour le don de sang au centre de la transfusion sanguine. Le taux de refus était 7.27% pour toute la durée de l’étude. Les donneurs hommes comptaient plus de 79% du nombre total de donneurs. L’évolution des types de dons a été inversée durant la période de l’étude avec plus de dons volontaires et moins de dons dans la famille. La séroprévalence totale a montré une augmentation de 0.20% en 2022 jusqu’au 4.65% en 2024. L’hépatite B était l’infection la plus détectée et ayant deux types de tests de dépistage ( HBs Ag et HBcAc) avec un taux de positivité de 4.28% en 2023 et 5.81% en 2024 pour le test HBcAc. Les taux les plus bas était chez les tests HIV et HCV qui enregistraient zéro tests positives pour les trois ans de l’étude. Ces résultats soulignent l’importance de l’amélioration des protocoles de dépistage et de la réglementation pour la sureté du sang.
Keywords: seroprevalence; blood donation; HIV; HBV; HCV; Syphilis امراض متنقلة; الالتهاب الفيروسي الكبديB; الالتهاب الفيروسي الكبديC; فيروسنقص المناعة المكتسبة séroprévalence; don de sang; HVB; HVC; Syphilis